International Journal of Modern Physics: A (Singapore : World Scientific, 1986)
Access available from 2001-
Title from cover.
Keywords: Particles (Nuclear physics) -- Periodicals; Field theory (Physics) -- Periodicals; Gravitation -- Periodicals; Cosmology -- Periodicals; Nuclear physics -- Periodicals; Natuurkunde